PENENTUAN SEKTOR UNGGULAN PEREKONOMIAN WILAYAH KABUPATEN BONE BOLANGO DENGAN PENDEKATAN SEKTOR PEMBENTUK PDRB - Fitri Amalia (ETIKONOMI, 2012)
Economic growth and its process are the main condition for the sustainability of the regional economic development. Because of the continuing population growth means economic needs also increase so that additional revenue required each year. This research is focused to determine the regional leading sector of Bone Bolango as the information and considerations in planning economic development. Location Quotient (LQ) and Shift Share are tools of analysis. Location Quotient analysis indicates agriculture, manufacture, finance, leasing and corporate services are base sectors in the Bone Bolango district. Shift Share analysis indicates that the competitive sectors are finance, leasing and corporate services. The results was indicate that the leading sector with the criteria developed, base, and competitive is finance and services sectorDOI: 10.15408/etk.v11i2.1893